CLINICAL CHARACTERISTICS OF ADVERSE REACTION TO RADIOCONTRAST MEDIA IN CHILDREN: A SINGLE CENTER EXPERIENCE - Kim, M.; Lee, B.; Choi, Y.; Suh, D. (Annals of allergy, asthma, & immunology, 2018)
Radiocontrast media are used widely in medical imaging to improve the diagnostic accuracy. However, studies on the adverse reaction of radiocontrast media in children are limited. We aimed to describe the characteristics of adverse reactions to radiocontrast media among children who had a computed tomography scan or magnetic resonance imaging in a tertiary university hospital. We retrospectively collected data on adverse reactions to radiocontrast media by the reporting system of a tertiary university hospital. We selected data of children under the age of 19 from July 2011 to December 2017 and analyzed characteristics of them. We focused mainly on the characteristics of the index case which is defined by the first adverse event of each subject. During the period, a total of 88050 radiocontrast media-enhanced imaging studies were performed and 184 cases were reported. A total of 71 were identified as index cases. Forty-nine (69.0%) were male and the mean age was 12.7±3.2 years. The incidence of radiocontrast media related adverse reactions was 0.09% and that of severe reactions was 0.002%. The most common features were skin manifestations (54.9%), followed by gastrointestinal symptoms (40.8%) and neuropsychiatric symptoms (7.4%). The adverse reactions to radiocontrast media rarely occur in children and the incidence of severe reaction is low. Most reactions are mild and are related to the skin and gastrointestinal system. This report would provide good evidence for establishing a management strategy in children awaiting imaging studies using radiocontrast media.